Analisis Soal Cerita Matematika pada Materi Bangun Datar Kelas IV Sekolah Dasar - Shela Anggraeni; Viktor Pandra; Lucy Arsi Purwasih (Journal of Elementary School (JOES), 2023)
This research aims to determine the quality of mathematics story questions in grade IV elementary school flat figures and find out how to prepare good mathematics story questions in grade IV elementary school. The method used in this research is a case study. The books analyzed in this research are "Happy Learning Mathematics" by Hobri, Susanto, Mohammad Syaifuddin, Dhika Elvira Maylistiyana, Hosnan, Anggraeny Endah Cahyanti, and Khoirotul Alfi Syahrinawati, the book "I'm Smart in Mathematics" by Zulkifli and Gito Suherman, the book "Mathematics for Elementary School/Madrasah Ibtidiyah Class IV" by Nanang Priatna and the book "Mathematics for Elementary/MI Class IV by Atmini Dhoruri. The results of this research are that the quality of the story questions in grade IV elementary school material is seen from the material aspect, the questions are in accordance with the criteria. Meanwhile, if seen from the construction aspect, the questions do not meet the criteria, because the questions analyzed do not contain scoring guidelines. Judging from the language aspect, the questions are in accordance with the criteria, Larena has used Indonesian which is in accordance with EYD. Writing good and correct questions must fulfill the three rules for writing descriptive questions, namely paying attention to aspects of material, construction and language.. Keywords: math essay questions, two-dimentional figure, grade IV Elementary School.